DNA methylation: Precise modulation of chromatin structure and dynamics. (August 2022) - Li, Shuxiang; Peng, Yunhui; Panchenko, Anna R.
Abstract: DNA methylation plays a vital role in epigenetic regulation in both plants and animals, and typically occurs at the 5-carbon position of the cytosine pyrimidine ring within the CpG dinucleotide steps. Cytosine methylation can alter DNA's geometry, mechanical and physico-chemical properties - thus influencing the molecular signaling events vital for transcription, replication and chromatin remodeling. Despite the profound effect cytosine methylation can have on DNA, the underlying atomistic mechanisms remain enigmatic. Many studies so far have produced controversial findings on how cytosine methylation dictates DNA flexibility and accessibility, nucleosome stability and dynamics. Here, we review the most recent experimental and computational studies that provide precise characterization of structure and function of cytosine methylation and its versatile roles in modulating DNA mechanics, nucleosome and chromatin structure, stability and dynamics. Moreover, the review briefly discusses the relationship between DNA methylation and nucleosome positioning, and the crosstalk between DNA methylation and histone tail modifications. Highlights: DNA methylation is involved in regulating chromatin dynamics and DNA accessibility. DNA methylation influences the geometry and mechanical properties of DNA. DNA methylation modulates nucleosome dynamics and positioning, in conjunction with a cross-talk with histone modifications. Experimental and computational methods reveal atomistic mechanisms of methylation-induced changes. Precise roles of DNA methylation in chromatin and nucleosome dynamics and stability remain under investigation.